The cobalt polycythemia action of ascorbic acid - Guzmán Barrón, Alberto (1944)
Experimental studies have polycythemias dual purpose; First, they can provide useful information for interpreting the other polycythemias mechanism occurring in man; also to better clarify constribuyen erythropoietic function. In our country, flushing height is a problem that deeply interested; production mechanism and implications physiologism have been studied by Professors Monge, Hurtado et al. In our stay in the United States, when we worked in the laboratories of Eleazar Barron, one of the topics we chose as research was polycythaemia caused by cobalt. At the same time we studied the oxidation of ascorbic acid and was discussed on the role of this vitamin in the mechanism of erythropoiesis reason that prompted us to investigate the action that ascorbic acid might exert on the development of polycythemia by cobalt and the study of the intimate mechanism of this polycythemia.